Mechanobiology of embryonic limb development - Prendergast, Patrick; NOWLAN, NIAMH CATHERINE; MURPHY, PAULA (My University, 2007)
Considerable evidence exists to support the hypothesis that mechanical forces have an essential role in healthy embryonic skeletal development. Clinical observations and experimental data indicate the importance of muscle contractions for limb development. However, the influence of these forces is seldom referred to in biological descriptions of bone development, and perhaps this is due to the fact that the hypothesis that mechanical forces are essential for normal embryonic skeletal development is difficult to test and elaborate experimentally in vivo, particularly in humans. Computational modeling has the potential to address this issue by simulating embryonic growth under a range of loading conditions but the potential of such models has yet to be fully exploited. In this article, we review the literature on mechanobiology of limb development in three main sections: (a) experimental alteration of the mechanical environment, (b) mechanical properties of embryonic tissues, and (c) the use of computational models. Then we analyze the main issues, and suggest how experimental and computational fields could work closer together to enhance our understanding of mechanobiology of the embryonic skeleton.
PUBLISHED
PMID: 17344536
Keywords: Embryonic muscle contractions; cartilage differentiation; immobilization; computer modeling; finite element analysis